Helper-free Production of Laboratory Grade AAV and Purification by Iodixanol Density Gradient Centrifugation - Crosson, Sean M. (Mol Ther Methods Clin Dev, 2018)
Adeno-associated virus (AAV) is one of the most promising gene therapy vectors and is widely used as a gene delivery vehicle for basic research. As AAV continues to become the vector of choice, it is increasingly important for new researchers to have access to a simplified production and purification protocol for laboratory grade recombinant AAV. Here we report a detailed protocol for serotype independent production of AAV using a helper-free HEK293 cell system followed by iodixanol gradient purification, a method described earlier.(1) While the core principals of this mammalian AAV production system are unchanged, there have been significant advancements in the production and purification procedure that serve to boost yield, maximize efficiency, and increase the purity of AAV preps. Using this protocol, we are able to constantly obtain high quantities of laboratory grade AAV particles (>5 × 10(12) vg) in a week’s time, largely independent of serotype.